New oxyuroid nematodes of the genera Ichthyouris and Spinoxyuris from South American freshwater fishes - Moravec, F; Thatcher, V E (Folia parasitologica, 2001)
Three hitherto unknown oxyuroid nematode species of the family Pharyngodonidae are described from the intestine of South American freshwater fishes, two of them being established as species new to science: Spinoxyuris annulata sp. n. from Myleus ternetzi (Norman) (Serrasalmidae) from French Guiana (Sinnamary River) and Ichthyouris ovifilamentosa sp. n. from Cichlasoma sp. (Cichlidae) from Amazonas (Negro River, São Gabriel da Cachoeira), Brazil. A third species, recovered from the same host as the latter (Cichlasoma sp.), was identified only as Ichthyouris sp. because of the absence of the male, although it probably also represents a new species. S. annulata differs from the only other congeneric species, S. oxydoras Petter, 1994, mainly in the absence of egg filaments, the location of an unpaired postanal papilla in the male, a distinctly longer spicule, and in an approximately double length of the body. Ichthyouris ovifilamentosa is closest to I. ro Inglis, 1962, differing from it principally in the structure of the cephalic end, the position of the excretory pore, and in the presence of filamented eggs. Ichthyouris sp. females differ from their congeners mainly in a characteristic structure of the cephalic end, the extent of lateral alae and the shape of their posterior ends, and in the character of egg filaments.
Keywords: Brazil; sladká voda; Perciformes; Female; Francouzská Guyana; Nematoda; hlístice; Brazílie; Animals; French Guiana; Microscopy, Electron, Scanning; ženské pohlaví; mužské pohlaví; Male; Fresh Water; zvířata; mikroskopie elektronová rastrovací